Team 19 in Vietnam : An Australian Soldier at War - Millie, David (Book collections on Project MUSE., 2013)
Historical accounts and memoirs of the Vietnam War often ignore the participation of nations other than Vietnam and the United States. As a result, few Americans realize that several members of the Southeast Asian Treaty Organization (SEATO), including Australia, allied with South Vietnam during the conflict. By the late 1960s, more than eight thousand Australians were deployed in the region or providing support to the forces there. In Team 19 in Vietnam, David Millie offers an insightful account of his twelve-month tour with the renowned Australian Army Training Team Vietnam in Quang.